Three new species of Baeoentedon Girault (Hymenoptera: Eulophidae) from China, with the first record of whitefly host association (Hemiptera: Aleyrodidae) - Wang, Zhu-Hong; Huang, Jian; Polaszek, Andrew (Zootaxa, 2014)
Three new species of Baeoentedon Girault (Hymenoptera: Eulophidae) are described from China, Baeoentedon balios Wang, Huang & Polaszek sp. nov., Baeoentedon bouceki Wang, Huang & Polaszek sp. nov. and Baeoentedon virgatus Wang, Huang & Polaszek sp. nov. Both female and male of Baeoentedon balios were reared from the whitefly Pealius spina (Singh) (Hemiptera: Aleyrodidae) on the bodhi tree Ficus religiosa L. (Urticales: Moraceae). The male and the whitefly host association of Baeoentedon are recorded for the first time. A key is also provided to females of the world species of the genus.